Comparative Studies on the Responses of Red Jungle Fowl and Commercial Broilers to Nutritional Manipulations - Soesanto, Iman Rohayu Hidayati (2000)
Experiments were conducted to compare the responses of the red jungle fowl (RJF) and commercial broiler chicken (CB) to choice feeding and dietary palm kernel cake (PKC). Traits measured were growth performance, protein and energy intakes, carcass characteristics, behaviour, heterophil/lymphocyte ratio, gut microflora and intestinal morphology. Evaluation of carcass characteristics at a common body weight (800 g) showed that RJF had heavier whole breast, thigh and drumstick than CB . Similarly, the muscle weight and muscle to bone ratio of those portions were greater in the former. The muscles of the breast and leg portions of RJF were of better quality than CB in term of protein, fat and cholesterol contents at a common body weight and at a common age (56 days old). Intense selection for growth may have caused an increase in the weight of abdominal fat, fat and cholesterol contents of breast and leg muscles in CB. The protein content, however, was lower in CB as compared to RJF. The choice feeding setting to meet the birds' own energy and protein requirements among basal diet, corn and soybean is acceptable for RJF but the growth performance was reduced in CB. In the choice feeding group, although both breeds consumed more basal diet, RJF consumed more soybean than corn and the opposite was noted for CB. The ratio of energy to protein intake for maximum growth of RJF up to Day 49 and CB up to Day 56 was calculated as 141 and 156, respectively. Among the CB fed CSC and LSC, the feed cost was reduced by 11.4% and 12.2% as compared to those provided a single diet (control). However the feed cost of RJF was not influenced by diet. Diet had no influence on behavioural parameters (eating, drinking, resting, walking, standing, bird-to-bird pecking and pecking of objects), however the heterophil to lymphocyte ratios (H/L) of choice fed birds were higher than those provided a single diet. The RJF were observed to be more active and agile compared to CB. The H/L ratio of RJF was higher than CB on Days 28 and 56, indicating that the confined RJF were more stressed than CB.